Makna Simbolik Tradisi MAPPACCI - Winda, Nur Hikmah; Suyuti, Nasruddin; Purwitasari, Paramitha (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study investigates the symbolic meaning of tradition and tries to explain the Mappacci symbols of Bugis Traditional weddings in Pomburea Village, East Kolaka Regency, Lambandia District. The employed qualitative descriptive research methodology in this research is Charles Sanders Pierce's semiotic analysis. The research data comes from the symbols used in the Bugis Traditional Mappacci wedding procession from the Pomburea Village community. This study shows that mapacci is used in three main stages: Mapacci, Barasanji, and Khamatal Al-Qur'an. 2) The Mappacci ceremony, which is interpreted as "clean" and "holy", aims to cleanse the soul and body of the bride and groom before starting household ark by cleaning everything, including "Mappaccing ati" (clean heart), "Mappaccing nawanawa" (clean mind), "Mappaccing pangkaukeng" (clean actions and behavior), and "Mappaccing ateka" (clean faith) and the symbolic meaning of the Mappacci process is: (1) The pillow represents honor, glory, dignity, and mutual respect (sipakatau); (2) the silk sarong represents self-respect, sitat istikamah, and perseverance; (3) the leaves of banana shoots represent mutual connection or continuous life; (4) the leaves of jackfruit represent noble ideals or hope and honesty; (5) the leaves of pacci represent cleanliness or purity; and (6) rice represents well-developed, blooming, and good living creatures.(8), means unity, (9) young coconut and brown sugar: both represent sweetness